ChemInform Abstract: Gold(I)‐Catalyzed N‐Desulfonylative Amination versus N‐to‐O 1, 5‐Sulfonyl Migration: A Versatile Approach to 1‐Azabicycloalkanes. Issue 50 (November 2016) - Miaskiewicz, Solene; Gaillard, Boris; Kern, Nicolas; Weibel, Jean‐Marc; Pale, Patrick; Blanc, Aurelien
Abstract: Various N‐sulfonyl protected 1‐azetidine‐2‐alkyn‐1‐ones are transformed in a gold(I)‐catalyzed N‐desulfonylation in the presence of an external O‐nucleophile to deliver 1‐azabicyclo[3.2.0]heptenes in high yields.